Nitrogen-doped carbon-coated hollow SnS2/NiS microflowers for high-performance lithium storage - Wang, Junhai; Zheng, Jiandong; Gao, Liping; Dai, Qingshan; Joo, Sang Woo; Huang, Jiarui (Frontiers of materials science, 2023)
Nitrogen-doped carbon-coated hollow SnS 2 /NiS (SnS 2 /NiS@N-C) microflowers were obtained using NiSn(OH) 6 nanospheres as the template via a solvent-thermal method followed by the polydopamine coating and carbonization process. When served as an anode material for lithium-ion batteries, such hollow SnS 2 /NiS@N-C microflowers exhibited a capacity of 403.5 mAh·g −1 at 2.0 A·g −1 over 200 cycles and good rate performance. The electrochemical reaction kinetics of this anode was analyzed, and the morphologies and structures of anode materials after the cycling test were characterized. The high stability and good rate performance were mainly due to bimetallic synergy, hollow micro/nanostructure, and nitrogen-doped carbon layers. The revealed excellent electrochemical energy storage properties of hollow SnS 2 /NiS@N-C microflowers in this study highlight their potential as the anode material.